Enhancing Ship Seaworthiness Supervision: A Study at KSOP Class II Kendari - Rachmianty, Andi; Yusri, Muhammad; Ningrat, Andi; Arifuddin, Andi Mursid Nugraha; Usman, Arif Fudddin; Rusnaedi (Naval Architecture Department, Kalimantan Institut of Technology, 2025)
Ship accidents often occur due to ships being unseaworthy to sail. The harbor master plays an important role in supervising the seaworthiness of ships and port activities. However, ship accidents still often occur due to the unseaworthiness of ships to sail. This study examines the level of performance of the harbor master at KSOP Class II Kendari. The method used is the Costumer Satisfaction Index (CSI). The questionnaire was given to the sample which was calculated using the Slovin calculation. The results of the questionnaire have gone through validity and reliability tests and show that the results obtained are valid and reliable. The percentage value of CSI obtained reached 84.95%. This figure indicates that customers are very satisfied with the performance of KSOP Class II Kendari. This shows that KSOP Class II Kendari has succeeded in meeting customer expectations and needs well.